Altered heartbeat perception sensitivity associated with brain structural alterations in generalised anxiety disorder. Issue 1 (12th February 2020) - Li, Hui; Zhang, Bin; Hu, Qiang; Zhang, Lanlan; Jin, Yi; Wang, Jijun; Cui, Huiru; Pang, Jiaoyan; Li, Chunbo
Abstract : Background: Palpitation is a common complaint in generalised anxiety disorder (GAD). Brain imaging studies have investigated the neural mechanism of heartbeat perception in healthy volunteers. This study explored the neuroanatomical differences of altered heartbeat perception in patients with GAD using structural MRI. Aims: Based on the strong somatic-interoceptive symptoms in GAD, we explored the regional structural brain abnormalities involved in heartbeat perception in patients with GAD. Methods: This study was applied to the a priori regions using neuroanatomical theories of heartbeat perception, including the insula, anterior cingulate cortex, supplementary motor area and prefrontal cortex. A total of 19 patients with GAD and 19 healthy control subjects were enrolled. We used the FMRIB Software Library voxel-based morphometry software for estimating the grey matter volume of these regions of interest and analysed the correlation between heartbeat perception sensitivity and the volume of abnormal grey matter. Results: Patients with GAD showed a significantly decreased volume of grey matter in their left medial prefrontal cortex, right orbital frontal cortex and anterior cingulate cortex. The grey matter volume of the left medial prefrontal cortex negatively correlated with heartbeat perception sensitivity in patients with GAD. Conclusions: It should be the first study that shows heartbeat perception is associated with brain structure in GAD. Our findings suggest that the frontal region may play an important role in aberrant heartbeat perception processing in patients with GAD, and this may be an underlying mechanism resulting in the abnormal cardiovascular complaints in GAD. This is hypothesised as a 'top-down' deficiency, especially in the medial prefrontal cortex. This will provide the foundation for a more targeted region for neuromodulation intervention in the future.